2018
DOI: 10.11607/jomi.5461
|View full text |Cite
|
Sign up to set email alerts
|

Guided Bone Regeneration with Collagen Membranes and Particulate Graft Materials: A Systematic Review and Meta-Analysis

Abstract: The aim of this meta-analysis was to evaluate different methods for guided bone regeneration using collagen membranes and particulate grafting materials in implant dentistry. Materials and Methods: An electronic database search and hand search were performed for all relevant articles dealing with guided bone regeneration in implant dentistry published between 1980 and 2014. Only randomized clinical trials and prospective controlled studies were included. The primary outcomes of interest were survival rates, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
180
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(192 citation statements)
references
References 42 publications
2
180
2
8
Order By: Relevance
“…Another key factor of the present study, differently from the protocol proposed by Degidi et al, is the use of a two stages surgical protocol instead of an immediate tooth replacement therapy. A recent review showed that implant survival rates for simultaneous and subsequent implant placement are similar and recommended simultaneous implant placement when possible . However, the use of a second surgical intervention, after ridge preservation and soft tissue healing, could allow a more prosthetically driven implant insertion, even avoiding a connective tissue graft …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key factor of the present study, differently from the protocol proposed by Degidi et al, is the use of a two stages surgical protocol instead of an immediate tooth replacement therapy. A recent review showed that implant survival rates for simultaneous and subsequent implant placement are similar and recommended simultaneous implant placement when possible . However, the use of a second surgical intervention, after ridge preservation and soft tissue healing, could allow a more prosthetically driven implant insertion, even avoiding a connective tissue graft …”
Section: Discussionmentioning
confidence: 99%
“…A recent review showed that implant survival rates for simultaneous and subsequent implant placement are similar and recommended simultaneous implant placement when possible. 38 However, the use of a second surgical intervention, after ridge preservation and soft tissue healing, could allow a more prosthetically driven implant insertion, even avoiding a connective tissue graft. 39 The present study demonstrated that the simultaneous use of OAOT approach and conical abutment might help in longitudinally stabilizing the peri-implant soft tissues.…”
Section: Soft Tissue Analysismentioning
confidence: 99%
“…Lateral ridge augmentation via GBR with the combination of a resorbable collagen membrane and particulate graft materials is a frequently reported technique in the literature, especially when treating dehiscence defects (Schwarz, Sahm, & Becker, ; Wang, Misch, & Neiva, ). Application of this technique produces equally high long‐term implant survival rates whether used subsequently to or simultaneously with implant placement (Wessing, Lettner, & Zechner, ). Therefore, a simultaneous approach is indicated whenever possible, as it reduces the number of surgeries, which lowers morbidity, reduces treatment time, and increases patient comfort (Wessing et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For dental implants to be placed in its functionally ideal position, three-dimensional hard-tissue reconstruction of recipient site by guided bone regeneration (GBR) is often necessary. [8] A vast variety of bone grafts and resorbable barrier membranes are available for the purpose of GBR technique. However, for successful hard-tissue regeneration, a bone graft should be biomechanically stable, able to degrade and replaced by new bone within an appropriate period.…”
Section: Discussionmentioning
confidence: 99%